Effect of Silver Nanoparticles Synthesized Using Betel Leaf Extract Added into Orthodontic Adhesive on the Bracket’s Tensile Bond Strength - Retnaningrum, Y. (Journal of International Dental and Medical Research, 2021)
This study investigates the effect of silver nanoparticles synthesized from betel leaf extract (SNBL) added into the orthodontic adhesive on the Bracket’s Tensile bond strength (TBS). Forty extracted premolars were randomly allocated into four groups of 10 as follows: the negative control (NC) group, and the treatment groups (1 SNBL (BL1), 3 SNBL (BL3), and 5 SNBL (BL5), which was incorporated with the orthodontic adhesive primer to form a nanoadhesive). The SNBL was incorporated at various concentrations into the orthodontic adhesive and visually analyzed using a transmission electron microscope (TEM). The brackets were then bonded, and TBS testing was performed using a Universal Testing Machine. The adhesive remnant index (ARI) value was evaluated by a stereoscopic microscope. The TBS-generated value was analyzed with ANOVA, whereas the ARI score was analyzed using the Kruskal-Wallis test (Î± = 0.05). There was a significant TBS difference (p < 0.05) between the four groups. The group bonded with 5 SNBL showed the significantly lowest TBS than the others 5.92 (0.96) MPa. In contrast, the NC group exhibited the significantly highest TBS value than the other groups 11.13 (1.57) MPa. The ARI scores between the four groups showed no statistically significant difference (p = 0.092). Orthodontics brackets failure location of NC, BL1, and BL3 dominated by ARI scores of 2, representing the bond failure between the adhesive-bracket interfaces. However, the BL5 group dominated by a score of 0, which indicated that bond failure occurred between the adhesiveenamel surfaces.We concluded that the addition of SNBL above 3% concentration into orthodontic adhesive materials decreases the TBS of orthodontic brackets but was still in the recommended adequate bond strength range value of 5.9–7.8 MPa.